PEDAGOGICAL FOUNDATIONS HOLISTIC AND SYSTEMATIC KNOWLEDGE DELIVERY TO STUDENTS IN THE SYSTEM OF NATURAL AND EXACT SCIENCES USING STEAM EDUCATIONAL TECHNOLOGY - Khodjamberdiev M. S. (Web of Journals Publishing, 2025)
This article presents the pedagogical foundations of imparting holistic, systematic knowledge to students using STEAM educational technology in the system of natural and exact sciences.
Keywords: Person-oriented education, STEAM educational technology, science, technology, engineering, art, and mathematics disciplines, career orientation.